STATUS KARIES PADA GIGI BERJEJAL DI SD NEGERI 12 TUMINTING - Malohing, Dewi; Anindita, P. S.; Gunawan, Paulina (e-GiGi, 2013)
Abstract: One of many dental problem has faced frequently by Indonesian people nowadays is dental caries, the other name for decay in teeth. The main factor leads into the caries is the setting of teeth (host) wich is out of the arch causing it hardly to be cleaned, tends to food and debris accumulated. These research aims to gain the image of the caries status for the crowding at tuminting 12th elementary school public. DMF-T index is used for this caries examination. The research is presented into descriptions from, take student who have been fom ten to twelve years old with crowding conditions as population, then uses the total sampling method to determine sixty seven of them as sample. The result for crowding of the caries distribution shows that the range of DMF-T number is 0.7. it belongs to the low category, based on category of DMF-T index by WHO. Keywords: caries, crowding. Â  Â  Abstrak: Salah satu masalah kesehatan gigi dan mulut yang dihadapi penduduk Indonesia adalah tingginya penyakit jaringan keras gigi atau karies. Karies gigi disebabkan oleh beberapa faktor. Salah satu faktor utama penyebab karies yaitu keadaan gigi (host), dimana posisi gigi dengan posisi keluar dari lengkung rahang, menyebabkan kesulitan pembersihan. Kondisi ini cenderung membuat makanan dan debris terakumulasi. Tujuan dari penelitian ini yaitu untuk memperoleh gambaran status karies pada gigi berjejal di SD Negeri 12 Tuminting. Pemeriksaan karies menggunakan indeks DMF-T. Penelitian ini merupakan penelitian deksriptif. Populasi dari penelitian ini yaitu siswa usia 10-12 tahun dengan kondisi gigi berjejal. Sampel berjumlah 67 orang dan pengambilan sampel dilakukan dengan metode total sampling. Hasil penelitian tentang distribusi karies pada gigi berjejal menunjukkan rata-rata jumlah DMF-T ialah 0,7 dan menurut kategori indeks DMF-T dari WHO termasuk pada kategori sangat rendah. Keyword: karies, gigi berjejal.